2016
DOI: 10.1016/j.cmi.2016.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Emerging infections caused by non- Aspergillus filamentous fungi

Abstract: There are three broad groups of non-Aspergillus moulds: the mucormycetes, the hyalohyphomycetes and the phaeohyphomycetes. Infections with these pathogens are increasingly reported, particularly in the context of increasing use of immunosuppressant agents and improved diagnostics. The epidemiology of non-Aspergillus mould infections varies with geography, climate and level of immunosuppression. Skin and soft-tissue infections are the predominant presentation in the immunocompetent host and pulmonary and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
71
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 170 publications
1
71
0
7
Order By: Relevance
“…Mucormycosis is the third most relevant invasive fungal infection (IFI) following candidiasis and aspergillosis in immunocompromised subjects leading to a significant degree of morbidity and mortality. 1 Globally, the incidence of mucormycosis is on the rise as a result of the expansion of the population at risk, but also because of the optimization of microbiology techniques for Mucor isolation. A population-based survey of IFI conducted in metropolitan France during 2001e2010 showed that the incidence of mucormycosis increased by 7.3% per year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucormycosis is the third most relevant invasive fungal infection (IFI) following candidiasis and aspergillosis in immunocompromised subjects leading to a significant degree of morbidity and mortality. 1 Globally, the incidence of mucormycosis is on the rise as a result of the expansion of the population at risk, but also because of the optimization of microbiology techniques for Mucor isolation. A population-based survey of IFI conducted in metropolitan France during 2001e2010 showed that the incidence of mucormycosis increased by 7.3% per year.…”
Section: Discussionmentioning
confidence: 99%
“…Mucormycosis is an emerging invasive fungal infection caused predominantly by the order e Mucorales e which encompasses the genera Rhizopus, Mucor, Litcheimia, Cunninghamella, Rhizomucor, Apophysomyces, and Saksenaea. 1 The disease accounts for extreme morbidity and mortality in adult and pediatric immunocompromised patients. The traditional predisposing conditions for mucormycosis include hematological malignancies, severe neutropenia, uncontrolled diabetes mellitus, trauma, prolonged use of corticosteroids and malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Since its first report in humans as Penicillium emersonii (2), there has been an increasing number of cases reported in both dogs (3,4,5) and humans (6). Nevertheless, it is likely that the number of human infections caused by this fungus has long been underestimated because of the lack of specificity of its morphological features and to subsequent misidentifications with some Penicillium or Paecilomyces species.…”
mentioning
confidence: 99%
“…With advances in antifungal prophylaxis drugs as well as technologies for fungal identification, the spectrum of invasive mold infection is expanding among immune compromised hosts . Colletotrichum (sexual state: Glomerella ) is one such emerging pathogen, for which we present the 14th described angioinvasive, extraocular infection in the known literature (see Table ) .…”
Section: Discussionmentioning
confidence: 99%